Integrated Suspended Growth Bioreactor System (i-SGBR) For Beverage Wastewater Denitrification and Sludge Degradation - AMINU, NASIRU (2017)
In the present study, effort has been made to assess treatability of beverage wastewater using three sequencially arranged suspended growth bioreactors, consisting of anoxic (ANX-C), aerobic (AER-C), and aerobic digester chambers (AD-C). Settler was incorported to separate sludge